2014
DOI: 10.1007/s00449-014-1204-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature and light intensity on growth, reproduction and EPS synthesis of a thermophilic strain related to the genus Graesiella

Abstract: Tunisian microalgae are diverse and rarely been studied. This study reports a first investigation of thermophile Chlorophyta isolated from mats community colonizing the geothermal springs in the north of Tunisia at water temperature 60 °C. In the study, the combined effect of temperature and light intensity was investigated on the cell growth, the mother and daughter cells abundance and the extracellular polymeric substances synthesis in batch culture of the isolated species. Three levels were tested for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 36 publications
0
22
2
Order By: Relevance
“…Previous studies demonstrated that the optimum (relative higher) temperature was 35-40 • C for some specific microorganisms on producing highest amount of EPS [24,26]. Nevertheless, in this study, 45 • C was the optimum temperature for EPS production.…”
Section: Eps Characterization and Sludge Properties Analysiscontrasting
confidence: 78%
“…Previous studies demonstrated that the optimum (relative higher) temperature was 35-40 • C for some specific microorganisms on producing highest amount of EPS [24,26]. Nevertheless, in this study, 45 • C was the optimum temperature for EPS production.…”
Section: Eps Characterization and Sludge Properties Analysiscontrasting
confidence: 78%
“…An explanation for this could be that P. tricornutum accumulates sEPS when the culture is in a stressed condition to protect cells from damage (Delattre et al 2016). Previous studies using the green alga Graesiella revealed that total EPS production increased with temperature (Mezhoud et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the whole consortium substantially remove the organic matter and nutrients in wastewater, with excellent settling characteristics allowing for biomass harvesting by gravity sedimentation (Quijano et al, 2017). While the genera such as Chlorella and Scenedesmus have been reported to be a suitable algal species (Gutzeit et al, 2005;Lee et al, 2013;Mezhoud et al, 2014;Vandamme et al, 2014;Shen et al, 2015;Kinnunen and Rintala, 2016;Arcila and Buitrón, 2017), so far, most bacteria identified in wastewater treatment using microalgal-bacterial systems belong to the phyla Bacteroidetes and Proteobacteria, such as Betaproteobacteria, Bacteroidia, Flavobacteria,Gammaproteobacteria (Su et al, 2011), Sphingobacteria, Terrimonas, and Hyphomon-as (Lee et al, 2013). More detailed knowledge on the interaction between different algal-bacteria species would facilitate better design.…”
Section: Sewage Millionaire-flocs In Wastewater Treatmentmentioning
confidence: 99%